Perwujudan nilai-nilai strategis revolusi mental pendidikan pada kearifan lokal pesantren - Asrori, Muhamad Abdul Roziq (Universitas Negeri Yogyakarta, 2017)
This research was aimed at describing Pesantren Gunung Jati (SGJ) in internalizing the strategic value of mental revolution in Islamic Senior High School students SGJ through local wisdom as well as revealing the strategies implemented to manage the its supporting points and obstacles. This research was qualitative approach and classified into case study. The result shows the values of